Analysis of fly ash-treated SDCM pile behavior through laboratory model tests - Zhou, Min; Zheng, Weifeng; Han, Yunshan; Tang, Changyi (Frontiers in Earth Science, 2024)
Fly ash, an industrial byproduct, has resulted in significant environmental pollution and poses a threat to human health due to its low recovery and utilization rate. Stiffened deep cement mixing (SDCM) piles, leveraging both the high lateral friction resistance of cement mixing pile socket and the high strength of concrete core pile, are widely employed in practice of soft ground improvement. However, to avoid damage to cement mixing pile socket, a higher amount of cement is often required, leading to not only elevated project costs but also conflicting with low-carbon environmental objectives. In tackling this concern, the introduction of fly ash as a partial substitute for cement in cement mixing pile socket offers a solution. This study delves into the vertical bearing mechanism of fly ash-treated SDCM piles through laboratory model tests. Results reveal that as the curing duration extends, the hydration rates of fly ash decrease relative to cement, being demonstrated by larger settlements at the top of fly ash-treated SDCM pile compared to that of standard SDCM pile. It is also found that elevated levels of hydration in cement mixing pile socket results in a heightened stiffness and an enhanced pile end resistance.